Utilization of Hybrid SIFCON to Improve Performance and Properties of Slab System Openings - Abuzaid, Esraa Kh.; Osman, S. A.; Mutalib, Azrul A.; Al-Zaidee, Salah R. (Salehan Institute of Higher Education, 2024)
This research aims to enhance Slurry Infiltrated Fibrous Concrete (SIFCON) by incorporating both long and short fibers, with the goal of increasing ductility and mechanical properties behavior. The study also evaluates the effectiveness of SIFCON in strengthening two-way reinforced concrete slabs with large openings. Various SIFCON mixes were created, integrating hooked-end fibers, micro steel fibers, and different volume ratios (Vf) of hybrid steel fibers (one-third, one-half, and two-thirds). A reference mix with 2% hybrid fiber-reinforced concrete (SFC) was formulated for comparison. Hybrid SIFCON samples demonstrated superior mechanical properties compared to those reinforced with hooked fibers, showing higher compressive strength, cylinder compressive strength, flexural strength, and direct tensile strength by 14%, 13.9%, 38.2%, and 58.2%, respectively, at 28 days, but a lower splitting tensile strength by 24%. Compared to micro steel fiber-reinforced samples, hybrid SIFCON exhibited higher compressive strength, cylinder compressive strength, flexural strength, and splitting tensile strength by 18.2%, 51%, 167.5%, and 43.6%, respectively, but a lower direct tensile strength by 7.4%. The study involved nine two-way square slabs with various mixtures of normal concrete, mortar-infiltrated fiber concrete, and full SIFCON. Control samples were constructed using normal-strength concrete. The application of SIFCON increased punching shear strength by 3.21% to 154.25% compared to the control samples. Doi: 10.28991/CEJ-2024-010-11-07 Full Text: PDF